Pengaruh Pengembangan Kawasan Perumahan Terhadap Sosial Ekonomi dan Minimalisasi Gejala Urban Sprawl - Muhammad Mulawarman Nasaruddin; Murshal Manaf; Haeruddin Saleh (Postgraduate Bosowa University, 2019)
Penelitian bertujuan untuk mengetahui pengaruh pengembangan kawasan perumahan terhadap sosial ekonomi masyarakat di Kota Palopo serta mampu mengetahui dan menganalisis pengembangan kawasan perumahan yang menimbulkan gejala urban sprawl. Jenis penelitian menggunakan kuantitatif deskriptif. Dengan metode Pengumpulan data menggunakan kuisioner sedangkan teknik analisis data menggunakan analisis deskriptif dan analisis spasial. Hasil penelitian menunjukkan bahwa pengembangan kawasan perumahan terhadap sosial ekonomi masyarakat telah mempengaruhi mata pencaharian dan penghasilan penduduk menjadi lebih baik. Jenis dan skala usaha mengalami peningkatan diakibatkan tingginya permintaan penunjang kehidupan masyarakat perumahan yang bersifat lebih konsumtif. Sementara mayoritas jenjang pendidikan masyarakat meningkat setelah terbangun be-berapa perumahan yang dilengkapi sarana pendidikan dan kesehatan yang lebih memadai. Sementara dibalik pengembangan kawasan perumahan di Kota Palopo menimbulkan gejala urban sprawl yang ditunjukkan dari 9 kecamatan di Kota Palopo, 4 kecamatan teridentifikasi sprawl yaitu Kecamatan Sendana, Kecamatan Mungkajang, Kecamatan Telluwanua dan Kecamatan Wara Barat. Kata Kunci: Urban Sprawl, Kawasan Perumahan, Sosial Ekonomi The study aims to determine the effect of the development of housing areas on the socio-economic community in the City of Palopo and find out and analyze the development of housing areas that cause urban sprawl symptoms. This type of research uses descriptive quantitative. The population is the entire community of Palopo City, amounting to 180,678. With Cluster Sampling obtained 4 districts as research samples and determination of the sample using the Slovin formula. Data collection by questionnaire while data analysis techniques using descriptive analysis and spatial analysis. The results showed that the development of housing areas on the socio-economic community in Palopo City had affected the people's livelihoods and income for the better. The type and scale of business has increased due to the high demand for supporting the life of a housing community that is more consumptive. While the majority of community education levels have increased after the construction of several housing facilities that are equipped with more adequate education and health facilities. While behind the development of a residential area in Palopo City, symptoms of urban sprawl are shown from 9 districts in Palopo City, 4 sprawl districts are identified, namely Sendana District, Mungkajang District, Telluwanua District and West Wara District. Keywords: Urban Sprawl, Settlement, Social Economy